Study on some problems in breeding insect-resistant Bt transgenic Japonica rice - SHEN Sheng-quan; WU Dian-xing; CUI Hai-rui; XIA Ying-wu; SHU Qing-yao (浙江大学学报. 农业与生命科学版)
Using the Bt rice “KMD” as the insect-resistant donor, three transgenic Japonica rice lines with high yield and insect resistance were successfully developed from crosses between the Bt rice and Japonica rice variety after pedigree selections lasting eight generations through GUS tissue staining-aided selection as well as laboratory and field insect-resistant evaluation. This fact indicates that the poor agronomic traits in the original transgenic rice plants can be improved through the conventional crossing breeding techniques. The effects of four kinds of breeding techniques, which involved screening the insect-resistant transgenic rice plants as revealed by GUS tissue staining, agronomic traits selection, bulk selection, field insect-resistance selection, were comparatively studied. The result showed that it is desirable to create insect-resistant Bt transgenic new Japonica rice via integral utilization of pedigree method and GUS tissue staining-aided selection.